Wash.ly Enteprise / Nurin Afreena Ahmad Jailani ... [et al.] - Ahmad Jailani, Nurin Afreena; Mohd Nazir, Norshamimie; Noor Azmi, Siti Nur Hanisah; Mohd Yunus, Muhammad Syazwan Fathullah; Abd Razak, Daniel Asyeed (2022)
Wash.ly Enterprise is a private firm that provides cleaning services to the general public, with a focus on working adults who are too busy or exhausted to clean their homes after a hard day at work. Because all of our employees are highly trained for their jobs, our service is guaranteed to be satisfactory and professional. Furthermore, we employ the most up-to-date technologies to ensure that the property we clean is pristine and dust-free. It is our highest responsibility to ensure that our clients are happy with our services. Wash.ly Enterprise is beneficial to a diverse group of people Wash.ly Cleaning and Sanitizing Services will concentrate on two socioeconomic groups. The first is rich, with only one life partner working. Despite the fact that the other life partner is at home and could clean, he/she chooses not to. The two-pay family is the second segment of the market on which we are concentrating our efforts. The two friends work long shifts and don't have much time to clean or do laundry. It's also critical that we're dependable and capable. We'll be handed a key to a piece of an empty house. We pay close attention to that trust. The head office of Wash.ly Enterprise is located in Bandar Seri Alam, Johor, where all client services are provided. Wash.ly Enterprise is noted for its great customer service, which ensures that no one will be forgotten or left behind when utilising the company's services. We also prepare multilingual customer service so that clients may communicate effectively despite language barriers. The website will be available in a variety of languages, ensuring that consumers have a positive experience contacting us